N‐Heterocyclic Carbene Iron Silyl Hydride Complexes. Issue 12 (20th November 2017) - Quintero‐Duque, Samuel; Li, Haoquan; Misal Castro, Luis C.; Dorcet, Vincent; Roisnel, Thierry; Clot, Eric; Grellier, Mary; Sortais, Jean‐Baptiste; Darcel, Christophe
Abstract: Reaction of N ‐heterocyclic carbene iron(0) tetracarbonyl complexes with hydrosilanes (triphenylsilane, methyldiphenylsilane and diphenylsilane) under UV irradiation (350 nm) afforded the octahedral N ‐heterocyclic carbene iron(II) silyl hydride complexes in yields up to 95 %, resulting from the oxidative addition of the hydrosilane. Eight iron silyl hydrides were obtained and characterized by NMR and X‐ray diffraction analysis. Noticeably, the geometry of the iron‐hydride complexes and the bent structures of the carbonyl ligands were rationalized by DFT calculations. Abstract :